Deciphering the birth region, formation, and evolution of ambient and transient solar wind using heavy ion observations - Rivera, Yeimy. J.; Higginson, Aleida; Lepri, Susan T.; Viall, Nicholeen M.; Alterman, B. L.; Landi, Enrico; Spitzer, Sarah A.; Raines, Jim M.; Cranmer, Steven R.; Laming, John M.; Mason, Emily I.; Wallace, Samantha; et al. (Frontiers in Astronomy and Space Sciences, 2022)
This paper outlines key scientific topics that are important for the development of solar system physics and how observations of heavy ion composition can address them. The key objectives include, 1) understanding the Sun’s chemical composition by identifying specific mechanisms driving elemental variation in the corona. 2) Disentangling the solar wind birthplace and drivers of release by determining the relative contributions of active regions (ARs), quiet Sun, and coronal hole plasma to the solar wind. 3) Determining the principal mechanisms driving solar wind evolution from the Sun by identifying the importance and interplay of reconnection, waves, and/or turbulence in driving the extended acceleration and heating of solar wind and transient plasma. The paper recommends complementary heavy ion measurements that can be traced from the Sun to the heliosphere to properly connect and study these regions to address these topics. The careful determination of heavy ion and elemental composition of several particle populations, matched at the Sun and in the heliosphere, will permit for a comprehensive examination of fractionation processes, wave-particle interactions, coronal heating, and solar wind release and energization that are key to understanding how the Sun forms and influences the heliosphere.